2020
DOI: 10.3390/metabo10080309
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Three Lycorine Type Alkaloids from Rhodolirium speciosum (Herb.) Ravenna Using pH-Zone-Refinement Centrifugal Partition Chromatography and Their Acetylcholinesterase Inhibitory Activities

Abstract: Preparative separation of three lycorine type alkaloids from Rhodolirum speciosum (Amaryllidaceae) was successfully carried out using pH-zone-refinement centrifugal partition chromatography (CPC) using the solvent system methyl-tert-butyl ether/acetonitrile/water (4:1:5, v/v/v) in descending mode. Using this system, Alkaloid 1 (165.7 mg, 88.2%, purity), 2 (60.1 mg, 97.7% purity) and 3 (12.3 mg, 84.4% purity) were obtained in one step. For structure elucidation, the pure alkaloids were subjected to spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The alkaloids were extracted using classical liquid‐liquid partition methodology [27] . Initially, 5 g of bulbs were degreased with hexane (40 mL) for 1 hour in an ultrasonic bath.…”
Section: Methodsmentioning
confidence: 99%
“…The alkaloids were extracted using classical liquid‐liquid partition methodology [27] . Initially, 5 g of bulbs were degreased with hexane (40 mL) for 1 hour in an ultrasonic bath.…”
Section: Methodsmentioning
confidence: 99%
“…90 Clivia miniata (Figure 19). 91,92 Lycorine (80) has broad biological activities including antivirus, antitumor antileukemia, anti-inflammatory, anti-angiogenesis, antibacterial, and antimalarial activities, 93 and it is considered as a lead compound for a new generation of anticancer drug design. 94 Recently, lycorine (80) was found to have antiviral activity against coronaviruses, MERS-CoV, SARS-CoV, and SARS-CoV-2, with IC50 values of 2.123, 1.021, and 0.878 μM, respectively, which was comparable to antiviral drug remdesivir.…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds Against Covi...mentioning
confidence: 99%
“…Figure 21. Structures of noscapine(89), chloroquine(90), ribavirin(91), favipiravir(92), rocaglamide(93), aglaroxin C (94), and zotatifin(95) …”
mentioning
confidence: 99%
“…The method provides many advantages over the conventional CPC, including a high sample loading capacity, and high purity and high concentration of the collected fractions [15]. pHzone-refining CPC has been successfully applied to the separation of alkaloids [16,17]. Previous studies have demonstrated the preparative separation of protopine and tetrahydropalmatine from C. decumbens and other medicinal plants by pH-zone-refining CCC [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%